How Selective Are Pharmacological Inhibitors of Cell-Cycle-Regulating Cyclin-Dependent Kinases? - Jorda, Radek; Hendrychová, Denisa; Voller, Jiří; Řezníčková, Eva; Gucký, Tomáš; Kryštof, Vladimír (Journal of medicinal chemistry, 2018)
Cyclin-dependent kinases (CDKs) are an important and emerging class of drug targets for which many small-molecule inhibitors have been developed. However, there is often insufficient data available on the selectivity of CDK inhibitors (CDKi) to attribute the effects on the presumed target CDK to these inhibitors. Here, we highlight discrepancies between the kinase selectivity of CDKi and the phenotype exhibited; we evaluated 31 CDKi (claimed to target CDK1-4) for activity toward CDKs 1, 2, 4, 5, 7, 9 and for effects on the cell cycle. Our results suggest that most CDKi should be reclassified as pan-selective and should not be used as a tool. In addition, some compounds did not even inhibit CDKs as their primary cellular targets; for example, NU6140 showed potent inhibition of Aurora kinases. We also established an online database of commercially available CDKi for critical evaluation of their utility as molecular probes. Our results should help researchers select the most relevant chemical tools for their specific applications.
Keywords: cyklin-dependentní kinasy; Cyclin-Dependent Kinases; Protein Kinase Inhibitors; Thiazoles; thiazoly; HCT116 Cells; HCT116 buňky; Humans; Quinolines; inhibitory proteinkinas; lidé; buněčný cyklus; Cell Cycle; chinoliny